Tang.kap Studio / Aliya Khadijah Abdul Razak ... [et al.] - Abdul Razak, Aliya Khadijah; Abu Bakar, Haikal; Shamsul Aizat, Nadia; Ab Halim, Puteri Nur Najwa; Yusni, Siti Nur Khairunnisa; Mohd Zaini, Siti Sarah (2021)
Tang.kap Studio is a sole company that offers photography and videography services and made available to consumers who want photographs taken as to commemorate special occasions. The business also creates social media content for corporations and designs logos after observing the demand for social media content as a marketing tool for businesses in Wilayah Persekutuan Kuala Lumpur and Selangor Darul Ehsan as well as the need for the rise of social media, which encourages people to disclose their personal lives. The business is headquartered in Seksyen 7, Shah Alam and it is owned by Haikal bin Abu Bakar as the founder of Tang.kap Studio. Before venturing into the photography and content creator business, he was an experience photographer and designer of Glam Magazine for six years before starting the firm of his own. The management of Tang.kap Studio consist of other five employees who dedicatedly work in the studio held liable in different roles. Aliya Khadijah binti Abdul Razak is responsible the department of Administration and Human Resource, Nadia binti Shamsul Aizat is accountable on the business’s financial, Puteri Nur Najwa binti Ab Halim is a photographer and videographer, Siti Nur Khairunnisa binti Yusni is the graphic designer, Siti Sarah binti Mohd Zani is responsible on Marketing and Sales department. Lastly, the owner, Haikal bin Abu Bakar is dependable to act as advisor, mastermind of generating ideas and work alongside with employees to handle customers. Tang.kap Studio serves the market by providing the needs and wants of the customers as they have identified that customers are hopping into the trend of posting photos and video of their personal life to social media platforms such as Instagram and Facebook. The studio seize the opportunity to help new business expanding their presence in the market by creating content for them that will assist in the marketing of the business. In order to keep the consumer relationship going, the business also offered promotions for certain occasions like festive season to allow customers capturing the memorable moments together.Tang.kap Studio marketing strategy is to focus solely on the studio setting and the affordable price which are high in demand within the youngsters nowadays.